Peralihan Hak Atas Tanah Sebagai Mahar: Kajian Normatif Perlindungan dan Kepastian Hukum Bagi Istri - Muhammad Ali Mabhan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Land holds significant economic, social, and cultural value in community life, including in the Bugis-Makassarese marriage tradition through the provision of a dowry in the form of land known as sunrang. Although the provision of sunrang is intended as a form of respect and security for women, its practice in Makassar City still raises legal issues, particularly related to unclear ownership status and potential disputes between wives, husbands, and extended families. This study aims to analyze the transfer of land rights granted as sunrang, the forms of legal protection for wives, and efforts to achieve legal certainty over the land. This study uses a normative legal research method with a statute approach, a conceptual approach, and a case approach. The analysis was conducted on laws and regulations, legal concepts, and cases relevant to the provision of land as a dowry. The results show that the provision of land as sunrang can result in a transfer of rights that requires clarity of legal status and strengthening of proof of ownership. Legal protection for wives can be strengthened by fulfilling administrative aspects, particularly the registration and recording of land rights transfers. Thus, the synergy between customary law and state law through certainty of land administration is an important step to prevent disputes and guarantee the protection of the wife's civil rights to the land she received as a marriage dowry